Involvement and Stress among Parents of Elementary Pupils on Modular Set-Up in Angeles City, Pampanga, Philippines - Miguel Carlo Alfonso; Kathrina Datu; Miles Rumill Dinn Gigante; Arjay Santiano; Renzo Santilices; Joseph Lobo (EDUCARE: Journal of Primary Education, 2022)
COVID-19-induced school disruptions have created significant interruptions in education across the world. A correlational study, which aims to determine if parental participation affects parental stress and demographic profile and socio-economic characteristics alter the association between the two variables among parents of elementary students in a modular set-up, Participants in this study should be: (1) Participating in schools that use a modular design, (2) Parents of elementary students in public elementary schools, (3) Angeles City citizens, (4) respondents between 21 and 50 years old and (5) either male or female. Researchers have utilized a self-administered online survey, and some parts of the survey were performed via house-to-house and face-to-face methods. Based on the findings, no significant relationship was observed between PI and PS. This study have recommended interventions to lessen parents’ stress while maintaining a high level of involvement in their children’s schooling.